A novel LSB steganographic method using partition and matching algorithms - Singh, Sukhjit; V.K Jain, Dr.; Amanpreet Singh, Dr. (International Journal of Engineering and Technology, 2018)
There is always a trade-off between embedding efficiency and hiding capacity of secret information. This paper presents a new ste-ganographic technique that improves the embedding efficiency and hiding capacity. For hiding information we extract LSB bits from 24-bit bmp color image. The LSB bits are joined to form an array of bits. An array is divided into N partitions depending upon the size of secret information to hide. The secret information is also divided into N partitions. Each data part finds the best possible matching location within each LSB array partition. The maximum bit matching depends upon the size of data partition, size of LSB array partition and the number of partitions used. The novelty of the proposed method is that the embedding capacity can be increased to desired level with lesser effect on embedding efficiency while maintaining security of embedded data. The paper presents efficient algorithms for bit manipulation that decreases the distortion and increases the embedding efficiency. The proposed technique shows an improvement over the existing LSB embedding methods.Â Â